Understanding the variations in grazing and rumination behaviours and their associations with production parameters in individual grazing dairy cows : a thesis presented in partial fulfilment of the requirements of the degree of Doctor of Philosophy in Animal Science at Massey University (Manawatū) New Zealand - Iqbal, Muhammad Wasim (Massey University, 2023)
This thesis aimed to understand: 1) the accuracy of an accelerometer-based sensor to monitor grazing and rumination behaviours in dairy cows; 2) grazing and rumination behaviour patterns and time budgets over 24 hours; 3) potential factors to influence grazing and rumination behaviours; and 4) effects of grazing and rumination behaviours on production parameters. To do this, data including, but not limited to, grazing time, rumination time, measures of cow performance (e.g., milk production and composition, body weight and body condition score), days in milk, and breeding worth index of 162 grazing dairy cows were collected for three consecutive lactation seasons (2018-2021). The analysis was performed on individual study years and results were reported separately for each year. First, the accuracy of AﬁCollar, an accelerometer sensor-based automated device to monitor and record grazing and rumination behaviours in dairy cows was evaluated for a grazing-based system. Spring-calved lactating cows (n = 48) wearing AﬁCollar were continuously visually observed for 8 hours (9 am to 5 pm) to quantify minutes per hour spent grazing and rumination. The behaviours being observed were also recorded with the AﬁCollar and compared with visual observations using Pearson’s correlation coefﬁcient (r), concordance correlation coefﬁcient (CCC), and linear regression. A strong association was found between the data collected by AfiCollar and the data obtained through visual observation for grazing time (r = 0.91, CCC = 0.71) and rumination time (r = 0.89, CCC = 0.80) with a signiﬁcant linear relationship between both datasets (p<0.05). Furthermore, variations in the temporal patterns (min/h) and time budgets (% min/day) of grazing and ruminating behaviours recorded using AfiCollar were evaluated in spring calving lactating (n = 162) Holstein-Friesian (HFR), Jersey (JE), and Holstein-Friesian Jersey crossbreed (KiwiCross, KC) cows in their different lactations (1st, 2nd, 3rd, 4th), and with different breeding worth index values (103151). A repeated measure design was performed in SAS using PROC MIXED considering the fixed effects of breed and lactation, the random effect of individual cows, and hours of the day as repeated measure to evaluate their effects on hourly patterns and time budgets of grazing, rumination, and idling behaviours. Regardless of the seasonal variations and feed consumed, cows spent most of their daytime grazing (with peaks around dawn and dusk) and most of their nighttime ruminating. Grazing and ruminating patterns were similar between cows from different breeds and lactations, however, JE cows grazed slightly longer than HFR and KC cows; and first-lactation cows grazed slightly longer than mature cows in their later lactations. The onset and cessation of grazing activity by the cows were adjusted according to varying day lengths by season. In addition, a general linear (PROC GLM) mixed model was fitted to test the effects of days in milk, breeding worth, breed, lactation year, individual cow, season, feed, and their interactions on variations in grazing time, rumination time and their relationship. Results indicated that grazing time varied among breeds in Year-2 and Year-3 and among lactation years in Year-1. Rumination time differed between breeds in only Year-3, and it remained the same within lactation years. Grazing time and rumination time varied among different seasons that were related to varying supplementary feeds. Days in milk, breeding worth (except Year-3), and the individual cow had effects (P<0.05) on grazing and rumination times. Grazing time and rumination time had a negative relationship with each other that varied between different seasons but remained the same among different breeds and lactation years. The variance in grazing and rumination times was mostly explained by individual cows (up to 24%), season (up to 12%), and feed (up to 8%). Moreover, results also showed that grazing and rumination times had positive associations with milk yield, fat, protein, and solids. Grazing time had negative and rumination time had positive associations with liveweight, while both grazing time and rumination time had negative associations with body condition score. Grazing time explained up to 1%, and rumination time explained up to 7% of the variance in milk yield, milk fat, protein, and solids. AfiCollar can reliably monitor grazing and rumination behaviours in dairy cows, however, its accuracy can be improved for a grazing-based system. The animal itself, the season, and the feed are the potential sources of variation in grazing and rumination behaviours and should be considered for management decisions to address the animal’s behavioural requirements. Grazing and rumination behaviours are moderately correlated with performance parameters and explain a small proportion of variance in animal productivity.
Keywords: Dairy cattle; Feeding and feeds; Behavior; Monitoring; automated behaviour monitoring; individual animal-based data; pasture-based dairy system; behaviour patterns and time budgets; behaviour variation; animal productivity; 300302 Animal management